Pengaruh budaya Mapalus Terhadap Partisipasi Masyarakat Dalam Pembangunan Di Desa Tombasian Atas Kecamatan Kawangkoan Barat Kabupaten Minahasa - LUMANTOW, MELDY ELSHADAY; Tampi, Gustaaf Budi; Londa, Very Yohanis (Sam Ratulangi University, 2017)
Abstract :This study aims to identify and analyze the magnitude of mapalus cultural influences againts societyparticipation in development in Tombasian Atas Village, Kawangkoan Barat Sub-District, MinahasaDistrict.Research Methods that the authors use in this study is a quantitative research method, is a research methodbased on the philosophy of positivism, used to examine the population or a particular sample. The samplingtechnique used is a simple random sample technique from research in Tombasian Atas Village as many as50 KK. Data analysis techniques used are simple linear regression analysis and simple correlation analysis.Based on the results of analysis using correlation pearson product moment obtained correlation coefficient(r) = 0.794 while the coefficient of determination (rÂ²) = 0.63. These results show that the coefficient ofdetermination of 63%. With this result it can be explained that the increase of society participation indevelopment is determined by mapalus culture by 63% while 37% is determined by other factors. Based onthe results of the above research, the hypothesis proposed can be accepted that there is a degree of linkageand determination power between mapalus culture againts society participation in development inTombasian Atas Village, Kawangkoan Barat Sub-District, Minahasa District. Based on the results ofsignificance test obtained value ð’•ð’‰ð’Šð’•ð’–ð’ð’ˆ = 12.141 at significant level (Î±) = 0.05 with degrees of freedom (df)= n - 2 = 48, then ð’•ð’•ð’‚ð’ƒð’†ð’ = 2.010. From the data it is obtained that ð’•ð’‰ð’Šð’•ð’–ð’ð’ˆ is greater than ð’•ð’•ð’‚ð’ƒð’†ð’ whereð’•ð’‰ð’Šð’•ð’–ð’ð’ˆ 12.141 > 2.010. Then ð‘¯ðŸ is accepted and ð‘¯ðŸŽ is rejected. It proves that there is a significant amountof influence between mapalus culture againts society participation in development in Tombasian AtasVillage, Kawangkoan Barat Sub-District, Minahasa District.Based on the result of the research, it can be concluded that the culture of mapalus has a strong influenceon society participation in development. So, the more often the society implements the culture of mapalusthen society participation in development will increase. Thus should increase cooperation, pay attention tohabits of helping each other, public interest, and become involved in rural development.Keyword : The Culture of Mapalus, Society Participation, Rural Development